Review of McDonald criteria (ORP-20) - Atefeh Eidi (Neurology Letters, 2023)
Diagnostic criteria in MS facilitate a rapid diagnosis of CIS or relapsing-remitting MS (RRMS) in patients who present with typical demyelinating syndromes. Previous criteria, including the Poser criteria, focused exclusively on clinical symptoms and signs. The emergence of the McDonald criteria in 2001 marked a new era in the diagnosis of MS where paraclinical criteria were incorporated so that the hallmark features of dissemination in space and dissemination in time could be met using a combination of clinical and MRI features The McDonald criteria have since undergone numerous revisions (2005, 2010, and most recently 2017). The latest revisions of the McDonald criteria have the benefit of higher sensitivity but also have a slight decrease in specificity compared with previous iterations Current MS diagnostic criteria facilitate the early diagnosis of MS in people presenting with typical clinical syndromes, allowing for the initiation of DMT in appropriate patients. However, the diagnosis can be challenging for several reasons, and diagnostic criteria should be used cautiously in patients presenting with atypical syndromes and those in special populations in whom the criteria have not yet been adequately validated. Clinical judgment and existing paraclinical tools are useful in minimizing misdiagnosis and facilitating an accurate diagnosis of MS.